Assessment of tumor enhancement by contrast‐enhanced CT in solid tumor‐bearing dogs treated with toceranib phosphate. Issue 4 (11th March 2020) - Takagi, Satoshi; Yamazaki, Hiroki; Izumi, Yusuke; Hanazono, Kiwamu; Hoshino, Yuki; Hosoya, Kenji
Abstract: In humans, contrast‐enhanced CT (CECT) has been used to indirectly assess the antiangiogenic effects demonstrated by a number of tyrosine kinase inhibitors. This retrospective, cross‐sectional study aimed to quantitatively evaluate changes in tumor contrast‐enhancement (CE) using CECT in solid tumor‐bearing dogs treated with toceranib phosphate (TOC). The changes in tumor size and CE were measured using the Hounsfield unit (HU) scale in CECT images before TOC treatment and between 30 and 90 days after initiating the treatment. Among the 36 dogs treated with TOC, eight (22.2%) showed a partial response, 22 (61.1%) showed stable disease, and six (16.7%) showed progressive disease. Thirty (83.3%) of 36 dogs showed a decrease in tumor CE (median: −20%, range: −1% to −48%) after initiating the treatment. The results indicated that tumor CE and size changes were observed in tumor‐bearing dogs that were treated with TOC; however, tumor CE was not significantly correlated with tumor regression. We suggest that these results could serve as pilot data to evaluate the antiangiogenic effects associated with TOC.